Suicide mortality and its behavioral characteristics in the city of Lima during the years 2017-2022 - Mendoza Saldaña, Yeny (2024)
Objective: To describe suicide mortality and its behavioral characteristics in Lima, Peru during the period 2017 - 2022. Methods: This was a descriptive observational study on suicide mortality and its behavioral characteristics found in Lima and its districts during the period 2017 - 2022. The sociodemographic characteristics and methods of suicide for the period 2017 - 2022 were described. Then, age-standardized mortality rates were estimated for Lima and its districts for each year and for the period 2017 - 2021. Results: There were 559 deaths by suicide during 2017 - 2022 in Lima with a ratio male/female of 2.6 and median age of 37. 68,78% were single, 44,54% had secondary education, 60,82% occurred at home with hanging being the main method of suicide with 70,98%.  The overall suicide rate was 5,52 per 100 000 population for Lima during the period 2017 - 2021. Mortality increased to a peak in 2019 and since then decreased. The districts with the highest mortality were Pucusana, Barranco and San Bartolo. Conclusions: Suicide mortality showed a decreasing trend since 2019 in Lima so it is imperative to maintain comprehensive long-term surveillance and implement prevention strategies and mental health care, particularly in the most affected districts and demographic groups. Key words: Suicide, Mortality, Lima